Anterior Segment OCT in Primary Angle Closure Disease Compared With Normal Subjects With Similar Shallow Anterior Chamber. Issue 2 (February 2022) - Xie, Qinghong; Ma, Ping; Patlidanon, Jutima; Saifee, Murtaza; Yonamine, Sean; Yu, Yinxi; Ying, Gui-Shuang; Yang, Yangfan; Li, Shuning; Han, Ying
Abstract : Précis: Compared with normal subjects with similar shallow anterior chamber depth (ACD), patients with primary angle closure disease (PACD) had narrower angle structures measured by swept-source optical coherence tomography (SS-OCT) at 250 μm from scleral spur (very root of iris), especially along oblique and vertical axis. Purpose: To examine anterior segment structures in normal subjects whose ACD was shallow on slit-lamp examination but did not meet the diagnostic criteria of PACD, and to compare them with PACD patients with similar ACD. Materials and Methods: Patients were recruited from glaucoma clinic at Zhongshan Ophthalmic Center. A total of 40 eyes from 29 PACD patients and 40 eyes from 34 normal subjects received full ophthalmic examination and CASIA SS-1000 OCT tests. PACD eyes and control eyes were 1:1 matched for ACD at 0 degree of scan. Generalized linear model that accounted for inter-eye correlation was used to compare differences between the 2 groups for intraocular pressure and SS-OCT parameters. P -values were adjusted for multiple comparisons using the Bonferroni method. Results: The PACD and control groups had similar age, but the PACD group had a significantly higher intraocular pressure (18.4 vs. 14.0 mm Hg, P =0.005). Angle parameters, representative of angle area, such as angle recess area and trabecular iris space area measured at 250 μm along axes of 90, 135, 225, and 315 degrees were significantly smaller in PACD group than those of control group (adjusted P <0.05), while most of angle parameters at 500 and 750 μm, volume parameters, and anterior chamber parameters, were similar (adjusted P >0.05). Conclusions: In PACD patients compared with normal subjects with similar anterior chamber shallowing, OCT findings measured at the iris root 250 μm from the scleral spur, especially in the oblique and vertical axes, including angle recess area and trabecular iris space area, may match gonioscopic findings more closely and provide further insight into mechanisms of PACD. Abstract : Supplemental Digital Content is available in the text.